Imagens e significados das novas alternativas de saúde : o caso das clínicas populares em São Paulo - Oliveira, Gabriela Laudares Albuquerque de (2018)
Historically, Brazil has been evolving with new solutions in order to supply the need for health of the population, both in public and private scope. Models that are aimed mainly at attending the poorest sections of society are constantly emerging. Popular clinics, private establishments that perform low-quality procedures such as appointments, exams and health treatments, have been configured as an option for the low-income public. The aim of the research is to comprehend the images that the consumer has about these new alternatives of supplementary health – the popular medical clinics. There are several studies on the Public and Private Health System in Brazil, in different areas of knowledge, however no studies about the Popular Clinics were found, not even about the repercussion of this phenomenon in the life of the consumers – phenomenon that is growing in the country and consolidated in U.S.. The main focus is to understand in which way the relationship of the consumer of popular class with the services of Popular Clinics occurs, the meanings involved and if this experience is translated into acess to health. This study also aims to provide the market with a view of the consumer’s perspective and thus support in the decision-making process and reformulation of its position in the market. For this purpose, it was opted for the qualitative methodological approach, through in-depth interviews, with semi-structured script, with consumers of popular clinics and content analysis. The results from the 12 interviews enable to state that the consumers of the popular clinics perceive a great change in the current model of the Brazilian health system, which brings a tranquility for the most basic health needs. However, such a model is not only far from being translated into access, but also indicates problems such as emergence of demands that may not be supplied, leaving stamped the structural inefficiencies of the country’s public health.